Women and politics in France 1958-2000 - Allwood, Gill (Routledge, 2000)
An essential guide to the role of women in the political life of France under the Fifth Republic. It shows that the unique political history of France ensures that it remains an important and exceptional example of women's participation in the politics of a Western European country. Its study is essential in order to have a complete understanding of women and politics today. This is the first English language study to capture the new enthusiasm engendered by the campaign for parity in 1992 which produced constitutional reform and a record number of deputies and ministers.